Structural complexity of filaments formed from the actin and tubulin folds. Issue 6 (1st November 2016) - Jiang, Shimin; Ghoshdastider, Umesh; Narita, Akihiro; Popp, David; Robinson, Robert C.
ABSTRACT: From yeast to man, an evolutionary distance of 1.3 billion years, the F-actin filament structure has been conserved largely in line with the 94% sequence identity. The situation is entirely different in bacteria. In comparison to eukaryotic actins, the bacterial actin-like proteins (ALPs) show medium to low levels of sequence identity. This is extreme in the case of the ParM family of proteins, which often display less than 20% identity. ParMs are plasmid segregation proteins that form the polymerizing motors that propel pairs of plasmids to the extremities of a cell prior to cell division, ensuring faithful inheritance of the plasmid. Recently, exotic ParM filament structures have been elucidated that show ParM filament geometries are not limited to the standard polar pair of strands typified by actin. Four-stranded non-polar ParM filaments existing as open or closed nanotubules are found in Clostridium tetani and Bacillus thuringiensis, respectively. These diverse architectures indicate that the actin fold is capable of forming a large variety of filament morphologies, and that the conception of the "actin" filament has been heavily influenced by its conservation in eukaryotes. Here, we review the history of the structure determination of the eukaryotic actin filament to give a sense of context for the discovery of the new ParM filament structures. We describe the novel ParM geometries and predict that even more complex actin-like filaments may exist in bacteria. Finally, we compare the architectures of filaments arising from the actin and tubulin folds and conclude that the basic units possess similar properties that can each form a range of structures. Thus, the use of the actin fold in microfilaments and the tubulin fold for microtubules likely arose from a wider range of filament possibilities, but became entrenched as those architectures in early eukaryotes.